PENINGKATAN JUMLAH KUNJUNGAN WISATAWAN PULAU MAITARA DI TENGAH PENDEMI COVID-19 - Mohbir Umasugi (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Tourism development on Maitara Island is based on several approaches, including increasing competitiveness, community involvement, environmental conservation, and improving the local economy. All of this is an effort to develop tourism to be able to increase the income of the surrounding community and at the same time increase regional income from the tourism sector. The purpose of this study is to analyze the increase in the number of tourists visiting Maitara Island amid the Covid-19 pandemic, so that it is hoped that it will be useful for the local government to maintain and even further improve services in the tourism sector. The data analysis method used in this research is descriptive qualitative to explore findings in the field. The results showed that when the Covid-19 epidemic occurred in 2020 the number of tourists visiting the Maitara Island tourist attraction increased from the previous year, where in the previous year or 2019 when there was no Covid-19 epidemic the number of tourists was only 2,104 whereas when the covid-19 epidemic occurred 19 there was an increase in the number of tourists to 5,600. This increase in the number of tourists is dominated by local tourists, this is influenced by the strict enforcement implemented by the government not to travel outside the area.